The Influence Of Animation Movie In Teaching Writing At The Tenth Grade Of SMK Nurul Huda Sukaraja - Ainur Rohmah; Munawaroh Munawaroh; Muhammad Zainuddin Afas (Lembaga Pengembangan Kinerja Dosen, 2023)
This thesis is entitled “The Influence of Animation Movies in Teaching Writing At The Tenth Grade of Smk Nurul Huda Sukaraja”. The objective of this study was to find out whether or not there is a significant difference between students who were taught by using animation movies and who were not taught by animation movies at the tenth-grade students of SMK Nurul Huda Sukaraja”. Therefore, this study was quantitative research, using experimental, methods and quasi-experimental design. Then, the population of the study covered and entire of the tenth-grade students of SMK Nurul Huda Sukaraja in the academic year 2023/2024 with a total students were 78 from four classes. The technique sampling was chosen by Purposive sampling. there were two groups the experimental groups (X-Multimedia A) with 19 students and the control group (X-Multimedia B) consists of 19 students. In this study, the writer used a written test as an instrument for collecting the data. The data obtained from independent t-test analysis, between the result of the post-test in the experimental group and control group. Based on the calculation by using an independent t-test, the writer found that tobtained was higher than ttable (5.561 > 2.021) at the significant level α = 0.05 in two-tailed test. It meant that there was an influence between the experimental group and the control group. So, the null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. It can be concluded that animation movie influence in teaching writing to the tenth grade students SMK Nurul Huda Sukaraja..